By algebraic handling and factoring, we conclude that the equivalent equation for the expression - 7 · x - 60 = x² + 10 · x is (x + 5) · (x + 12) = 0.
In this question we have a quadratic function which must be factored by algebraic handling:
- 7 · x - 60 = x² + 10 · x
x² + 10 · x + 7 · x + 60 = 0 Compatibility with addition/Modulative property
x² + 17 · x + 60 = 0 Definition of addition
(x + 5) · (x + 12) = 0 x² + (- a - b) · x + a · b = 0/Result
By algebraic handling and factoring, we conclude that the equivalent equation for the expression - 7 · x - 60 = x² + 10 · x is (x + 5) · (x + 12) = 0.
To learn more on quadratic equations: https://brainly.com/question/5975436
#SPJ1